2020
DOI: 10.1177/1177271920903038
|View full text |Cite
|
Sign up to set email alerts
|

Association of Functional Polymorphism in Protein Tyrosine Phosphatase Nonreceptor 22 (PTPN22) Gene with Vitiligo

Abstract: The protein tyrosine phosphatase nonreceptor 22 (PTPN22) is associated with susceptibility to autoimmune diseases. The functional polymorphism in PTPN22 at 1857 is a strong risk factor for vitiligo susceptibility in Europeans; however, controversy exits in other populations. Present study was aimed to determine whether the PTPN22 C1857T polymorphism confers susceptibility to vitiligo in Saudi Arabians. Genomic DNA was extracted and amplified using tetra primer amplification-refractory mutation system polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…In our study we showed statistically significant differences ( p = 0.001) in the frequency of genotypes between the experimental and the control group, what confirms the association of the 1858 C/T polymorphism of the PTPN22 gene with vitiligo. CT heterozygotes were the most frequent genotype in the experimental group, what is consistent with other studies [ 46 , 47 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study we showed statistically significant differences ( p = 0.001) in the frequency of genotypes between the experimental and the control group, what confirms the association of the 1858 C/T polymorphism of the PTPN22 gene with vitiligo. CT heterozygotes were the most frequent genotype in the experimental group, what is consistent with other studies [ 46 , 47 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…They concluded that this allele predisposes to vitiligo in Europeans, but not in Asians and Americans. In recent studies, Huraib et al [46] and Rajendiran et al [47] showed an association of this polymorphism in the Saudi and South Indian Tamil populations, respectively. However, Akbas et al [48] did not observe such correlations in the Turkish population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] Yet, the CT genotype is not exclusive for AIT, it was reported in children with diabetes mellitus type 1 (T1DM), where it is more dominant followed by CC and TT, in vitiligo and immune skin diseases. [18][19][20] Central hypothyroidism was observed in 83.9% of participants. According to Pierce et al (2017), thyroid dysfunction in DS was more common than in non-DS children, but the disorder was mostly transient.…”
Section: Discussionmentioning
confidence: 99%
“…2 Reductions in beauty, self-esteem, and quality of life occur in patients with vitiligo. 3 Currently, the main treatments for vitiligo are non-labeled immunosuppressants, such as systemic or topical steroids, topical calcium-regulated neurophosphatase inhibitors, combined with the use of ultraviolet light. 4 In addition, drug candidates for ameliorating vitiligo include targeting the Janus kinase, and Wnt signaling, and microRNAs, or regulatory T cells.…”
Section: Introductionmentioning
confidence: 99%